Success Factors in New Product Launch - Rienecker, Maximilian Gerd Jean (2011)
This research report has sought to identify the success factors of new product launch. For this purpose, it has adopted a qualitative as well as quantitative research methodology. That is, based on four case studies investigating the new product launch of four consumer goods companies, together with literature review, a conceptual model was developed. Subsequently a pilot study was conducted to test this model, i.e. a web based questionnaire was created and sent out to companies across four countries, i.e. Germany, France, USA, and the UK. The case studies indicate that companies involve network partners such as suppliers, consumers, customers, consultants, and academia into strategic and tactical launch decisions. Furthermore, the use of the Internet and Social Media throughout the new product launch process has become the rule rather than the exception. Literature review has further shown that lean launch strategies and logistics personnel involvement are important for NPL success. Accordingly, the model was built around these factors and hypothesized that the involvement of a company’s network into strategic and tactical launch decisions, the use of Internet and Social Media for various launch activities such as market research, promotion and distribution, the use of lean launch logistics strategy, and the involvement of logistics personnel during launch are positively related to market performance. The findings of the pilot study reveal that network involvement is very low. Further, consultants’ involvement into tactical launch decisions negatively impinges on new product launch success. Besides this, no other network partner’s involvement was found significant in explaining new product launch success. While lean launch strategies were not found to be significantly positively related to launch success, logistics personnel involvement was. Despite the finding that Social Media is significantly positively related to launch success, the use of the Internet for feedback purposes is found to be significantly negatively affecting product performance. The use of the Internet for promotion or distribution purposes was not significant. Nevertheless, due to the nature of the pilot study, i.e. a low sample of 24 respondents, these findings have to be taken with caution and need to be further investigated by future research.